Tendencies and characteristics of public fitness behavior in the digital era: an Internet ethnography study based on the K Community in China - Jia, Chen; Ye, Songdong (Frontiers in Public Health, 2024)
In the era of digital intelligence, the integration of media technologies into fitness activities has led to a new and distinct landscape of public fitness. This study utilizes Internet ethnography as a qualitative research methodology. The objective is to analyze the patterns and attributes of widespread fitness practices in China throughout the digital era by monitoring the daily activities of digital fitness participants in the K-community. The study demonstrates that as media technology and network culture progress, the group engaged in digital fitness increasingly displays fragmentation, digitization, entertainment, ritualization, and socialization in their quest for varied and intricate exercise experiences. The evolution and alteration of fitness behavior not only mirrors the functioning principles of modern media technology, but also replicates the essence of popular culture in the digital era. This study investigates the influence of media technology on the fitness industry during the digital age. Employing Internet ethnography, it analyzes the daily routinespractices of for individualsdigital fitness users residing in the K community. The results demonstrate an increasing fragmentation, digitalization, entertainment, ritualisationformalization, and socialization among those engaged in digital fitness. The transformation of physical activities and fitness behavior aligns with the operational mechanisms of media technology and the prevailing culture of the digital era. The research underscores the distinctive attributes of this digital era.